Afiksasi Fi’il Pada Surah An-Naba’: Kajian Morfologi - Fajrotuz Zahroh; Muhammad Nasiruddin; Salsa Hauna Ajidin (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2026)
This study aims to describe the form of fi’il affixation and analyze the grammatical meaning produced in Surah An-Naba’. This study uses a qualitative approach with a library research type. The research data are in the form of verses in Surah An-Naba’ containing fi’il, which are then analyzed using Arabic morphological and grammatical analysis techniques. The results of the study indicate that there are three forms of fi’il affixation, namely prefix, suffix, and confix. Prefix functions as a subject and time marker in fi’il muḍāriʻ, suffix functions as an actor marker (fa‘il), while confix indicates a combination of subject and number. The resulting grammatical meaning includes indicating time (past, present, and future), actor (subject), and number (mufrad and plural). Thus, affixation not only affects word form but also determines grammatical meaning in sentence structure. This research contributes to the study of Arabic morphology, particularly in understanding the relationship between affixation forms and grammatical meaning in the Qur'an.